Effectiveness and safety of tenofovir amibufenamide and its comparison with tenofovir alafenamide in patients with chronic hepatitis B: results from a retrospective real-world study - Lanqing Li; Jing Zhou; Yujing Li; Fada Wang; Dongmei Zhang; Menglan Wang; Yachao Tao; Enqiang Chen (Frontiers Media S.A., 2023)
Background/aim: Tenofovir amibufenamide (TMF) has shown potent antiviral efficacy in randomized clinical studies. This study aimed to reveal the effectiveness and safety of tenofovir amibufenamide in the real world and compared tenofovir amibufenamide to tenofovir alafenamide (TAF) in patients with chronic hepatitis B (CHB).Methods: In this retrospective study, tenofovir amibufenamide-treated chronic hepatitis B patients were divided into treatment-naive (TN) and treatment-experienced (TE) groups. Furthermore, tenofovir alafenamide-treated patients were enrolled using the propensity score matching method (PSM). We assessed the virological response (VR, HBV DNA < 100 IU/mL) rate, renal function, and blood lipid changes during 24 weeks of treatment.Results: Virologic response rates at week 24 were 93% (50/54) in the treatment-naive group and 95% (61/64) in the treatment-experienced group. The ratios of alanine transaminase (ALT) normalization were 89% (25/28) in the treatment-naive group and 71% (10/14) in the treatment-experienced group (p = 0.306). Additionally, serum creatinine decreased in both the treatment-naive and treatment-experienced groups, (−4.44 ± 13.55 μmol/L vs. −4.14 ± 9.33 μmol/L, p = 0.886), estimated glomerular filtration rate (eGFR) increased (7.01 ± 12.49 ml/min/1.73 m2vs. 5.50 ± 8.16 ml/min/1.73 m2, p = 0.430), and low-density lipoprotein cholesterol (LDL-C) levels increased (0.09 ± 0.71 mmol/L vs. 0.27 ± 0.68 mmol/L, p = 0.152), whereas total cholesterol/high-density lipoprotein cholesterol (TC/HDL-C) levels decreased continuously from 3.26 ± 1.05 to 2.49 ± 0.72 in the treatment-naive group and from 3.31 ± 0.99 to 2.88 ± 0.77 in the treatment-experienced group. Using propensity score matching, we further compared virologic response rates between the tenofovir amibufenamide and tenofovir alafenamide cohorts. Virologic response rates in treatment-naive patients were higher in the tenofovir amibufenamide cohort [92% (35/38) vs. 74% (28/38), p = 0.033]. Virologic response rates in treatment-experienced patients showed no statistical difference between the tenofovir amibufenamide and tenofovir alafenamide cohorts.Conclusion: Tenofovir amibufenamide had profound antiviral effectiveness and no adverse effects on renal function or blood lipids. Additionally, tenofovir amibufenamide was more efficient than tenofovir alafenamide in inhibiting viral replication, which needs to be demonstrated in future studies.